A survey of Sub-Saharan African medical schools - Chen Candice; Buch Eric; Wassermann Travis; Frehywot Seble; Mullan Fitzhugh; Omaswa Francis; Greysen S; Kolars Joseph C; Dovlo Delanyo; El Gali Abu Bakr Diaa; Haileamlak Abraham; Koumare Abdel; et al. (BMC, 2012)
Abstract Background Sub-Saharan Africa suffers a disproportionate share of the world's burden of disease while having some of the world's greatest health care workforce shortages. Doctors are an important component of any high functioning health care system. However, efforts to strengthen the doctor workforce in the region have been limited by a small number of medical schools with limited enrolments, international migration of graduates, poor geographic distribution of doctors, and insufficient data on medical schools. The goal of the Sub-Saharan African Medical Schools Study (SAMSS) is to increase the level of understanding and expand the baseline data on medical schools in the region. Methods The SAMSS survey is a descriptive survey study of Sub-Saharan African medical schools. The survey instrument included quantitative and qualitative questions focused on institutional characteristics, student profiles, curricula, post-graduate medical education, teaching staff, resources, barriers to capacity expansion, educational innovations, and external relationships with government and non-governmental organizations. Surveys were sent via e-mail to medical school deans or officials designated by the dean. Analysis is both descriptive and multivariable. Results Surveys were distributed to 146 medical schools in 40 of 48 Sub-Saharan African countries. One hundred and five responses were received (72% response rate). An additional 23 schools were identified after the close of the survey period. Fifty-eight respondents have been founded since 1990, including 22 private schools. Enrolments for medical schools range from 2 to 1800 and graduates range from 4 to 384. Seventy-three percent of respondents (n = 64) increased first year enrolments in the past five years. On average, 26% of respondents' graduates were reported to migrate out of the country within five years of graduation (n = 68). The most significant reported barriers to increasing the number of graduates, and improving quality, related to infrastructure and faculty limitations, respectively. Significant correlations were seen between schools implementing increased faculty salaries and bonuses, and lower percentage loss of faculty over the previous five years (P = 0.018); strengthened institutional research tools (P = 0.00015) and funded faculty research time (P = 0.045) and greater faculty involvement in research; and country compulsory service requirements (P = 0.039), a moderate number (1-5) of post-graduate medical education programs (P = 0.016) and francophone schools (P = 0.016) and greater rural general practice after graduation. Conclusions The results of the SAMSS survey increases the level of data and understanding of medical schools in Sub-Saharan Africa. This data serves as a baseline for future research, policies and investment in the health care workforce in the region which will be necessary for improving health.